Social Inequality, Childhood and the Media A Longitudinal Study of the Mediatization of Socialisation - Paus-Hasebrink, Ingrid; Kulterer, Jasmin; Sinner, Philip; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This open access book presents a qualitative longitudinal panel-study on child and adolescent socialisation in socially disadvantaged families. The study traces how children and their parents make sense of media within the context of their everyday life over twelve years (from 2005 to 2017) and provides a unique perspective on the role of different socialisation contexts, drawing on rich data from a broad range of qualitative methods. Using a theoretical framework and methodological approach that can be applied transnationally, it sheds light on the complex interplay of factors which shape children$1 (Bs socialisation and media usage in multiple ways. .s
Chapter 1 -- Framing the Study.-Chapter 2 -- Social Inequality, Childhood and the Media.-Chapter 3 -- The Role of Media Within Young People's Socialisation: A Theoretical Approach.-Chapter 4 -- The Methodological Approach of the Long-Term Study -- Chapter 5 - Family Descriptions.-Chapter 6 - Socialisation in Different Socialisation Contexts.-Chapter 7 - The Interplay Between Family and Media as Socialisation Contexts: Parents' Mediation Practices -- Chapter 8 -- The Typology of Socially Disadvantaged Families -- Chapter 9 -- Discussion and Conclusion.
Keywords: Communication; Digital media; Sociology; Social groups; Youth$1 (BSocial life and customs.s; Media and Communication; Digital and New Media; Sociology of Family, Youth and Aging; Youth Culture